Double-skin façade thermal monitoring. - Marques da Silva, F. (2017)
This paper concerns to the post-occupancy monitoring of a building sited in Lisbon with transparent double-skin façades (DSF). This is the first of an enlarged monitoring program covering other buildings and weather conditions aiming to clarify under which climate and performing conditions this architectural solution is acceptable. Within this campaign an enlarged set of parameters were measured, covering from outdoor conditions to indoor comfort. The present paper focus is the thermal behaviour of the façade.